Comparison of Lipid and Lipoprotein values in men and women differing in training status - Imamoglu, O.; Atan, T.; Kishali, N. F.; Barmaoglu, G.; Akyol, P.; Yildirim, K. (Biology of Sport, 2005)
The aim of this study was to compare plasma triglyceride and lipoprotein concentrations of male and female subjects of different training levels and to examine the risks of cardiovascular diseases. For this purpose, 20 male athletes from the National Turkish Wrestling Team (age 23.5±1.25 years) and 44 male and 51 female students (ages 21.7±1.72 and 20.20±1.68 years, respectively) from physical education and sports department and 40 sedentary females (age 21.14±1.72 years) participated this study. Trigliceride (TG), total cholesterol (TC), HDL-C and LDL-C levels were determined by Hitachi 717 autoanalyser. Apo A-1, Apo B and Lp(a) levels were determined by Behringer Nephelometer 100. Maximum oxygen consumption (VO2max) values were predicted from the results of 12 min run lest and the maximalanaerobic power values were measured by Jump Meter Instrument. There were no significant differences in plasma TC, TG and small lipoprotein a (Lp (a)) values between four groups (p>0.05). No significant differences were found in HDL-C, LDL-C, apolipoprotein AI (Apo-Al) and apolipoprotein B100 (Apo-B) values between wrestlers and male students; and between female students and sedentary females (p>0.05). HDL-C values of female students and sedentary females were significantly higher when compared with wrestlers and male students (41.52 and 40.93 mg/dl versus 51.92 and 50.10mg/dl). However, LDL-C values were found to be lower in females than in males (121.83 and 101.10 mg/dl as oppose to 97.7 and 98.4mg/dl). Significant (p<0.05) of differences were found between wrestlers and both female groups. Although the wrestlers' training levels were higher than that of male students, their TG and lipoprotein values were not different. These variables were not different between female groups either. These results showed that in young subjects medium and high level of exercises did not cause significant differences in TG and lipoprotein levels, but the gender differences were very pronounced. Neither in wrestlers nor in the remaining groups of subjects the lipid and lipoprotein profiles indicate risk of coronary heart disease.